An Overview of the Law of the Sea - Das, Amruta; Mishra, Amrita (International Journal of Psychosocial Rehabilitation, 2025)
This research paper discusses the various aspects of the Law of the Sea, especially the territorial sea which has within its ambit, various concepts such as internal waters, territorial sea, contiguous zone and exclusive economic zone. The paper also talks about the laws that govern the law of the Sea, which are UNCLOS I, II and III. The paper concludes with discussing the importance of the law and how the various disputes have helped structuralize the existing laws.